The effect of injector nozzle holes on diesel engine performance - Dinh , Tan Ngoc; Do , Van Dung (Journal of Technical Education Science, 2020)
Nowadays, Diesel engines are so popular, especially in the field of transportation and marine. However, in order to increase power, reduce consumption and emission, further improvement is necessary. In this research, AVL - FIRE software was used to study the effect of injectors to the combustion chamber, the injection hole diameter related to: power, torque as well as exhaust gas on Diesel engine (Kia JD - K3500 Diesel engine). The results show that with d = 0.16mm, the best power, low fuel consumption but high emissions. And d=0.2mm, the lowest emission. The results of this research improve fuel injectors and diesel engine performance.